The effectiveness of the Malaysian studies course in fostering patriotism among students in institutions of higher education - Ku Samsu, Ku Hasnita; Sulaiman, Mohd Hafiz
This study was designed to analyze and compare the level of patriotism awareness among students before and after completing the courses based on the elements of Malaysian Studies. A total of 938 students had been chosen from two Public Higher Educational Institutions namely Universiti Putra Malaysia (UPM) and Universiti Kebangsaan Malaysia (UKM); and two Private Higher Educational Institutions namely Lim Kok Wing University of Creative Technology (LKW) and Multimedia University (MMU). The data collection had been conducted in two phases, which is pre-test and post-test and was analyzed using descriptive statistical analysis, such as means, percentage and frequency. Besides, inference statistical analysis by way of paired sample t-test had also been used.